2019
DOI: 10.1021/acsami.9b01307
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticle-Decorated g-C3N4 Nanosheets for Controlled Generation of Reactive Oxygen Species upon 670 nm Laser Illumination

Abstract: Conventional photosensitizer-based photodynamic therapy is triggered by UV-light irradiation and depends on oxygen. However, it is hard to be applied to the deep and hypoxic tumor. To address this issue, we reported a new kind of g-C 3 N 4 nanosheet decorated with gold nanoparticles (AuNPs), which could generate a high amount of reactive oxygen species (ROS) under a 670 nm laser irradiation in an oxygen-free environment. This synthesized semiconductor−metal heterojunction served as a superior photodynamic agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(36 citation statements)
references
References 40 publications
3
33
0
Order By: Relevance
“…Moreover, Dai et al fabricated g ‐C 3 N 4 coated with Au nanoparticles by the joint approach of liquid‐phase exfoliation and photo‐deposition ( Figure A). [ 78 ] As a semiconductor material with great photocatalytic activity, g ‐C 3 N 4 has a wide bandgap of 459 nm, which severely hinders its application in PDT. They reported that Au makes use of the laser energy to move and accumulate electrons in the CB of g ‐C 3 N 4 , which improves the separation efficiency of photoexcited charges and facilitates ROS generation from H 2 O (Figure 14B).…”
Section: Application Of Different Heterojunction Photocatalysts In Bi...mentioning
confidence: 99%
“…Moreover, Dai et al fabricated g ‐C 3 N 4 coated with Au nanoparticles by the joint approach of liquid‐phase exfoliation and photo‐deposition ( Figure A). [ 78 ] As a semiconductor material with great photocatalytic activity, g ‐C 3 N 4 has a wide bandgap of 459 nm, which severely hinders its application in PDT. They reported that Au makes use of the laser energy to move and accumulate electrons in the CB of g ‐C 3 N 4 , which improves the separation efficiency of photoexcited charges and facilitates ROS generation from H 2 O (Figure 14B).…”
Section: Application Of Different Heterojunction Photocatalysts In Bi...mentioning
confidence: 99%
“…Li and Yang reported 5-10 nm gold nanoparticle (AuNP) could absorb 670 nm light energy, and excited electrons were injected into g-C 3 N 4 nanofilms, which extended the process of photoinduced charge separation and delayed the combination of electron-hole pairs to enhance type I PDT. 90,91 PS-Doped g-C 3 N 4 for PDT…”
Section: G-c 3 Nmentioning
confidence: 99%
“…Although AuNP-photosensitizer conjugates are the most important nanoplatforms for cancer PDT, conventional photosensitizer-based PDT is induced by light illumination and depends on oxygen, thus fails to be effective in hypoxic tumors. To address this issue, Yang et al [82] developed an excellent photodynamic agent, g-C 3 N 4 loaded with AuNPs, for PDT of hypoxic tumors. The integration of AuNPs into the nanoplatform significantly increased the electron/hole separation because of enhanced optical absorption efficiency at 670 nm, which leads to high level of ROS generation through a photocatalytic water-splitting reaction (Figure 7B).…”
Section: Pdtmentioning
confidence: 99%
“…(B) Reproduced with permission. [82] Copyright 2019, American Chemical Society A, B) Reproduced with permission. [89] Copyright 2020, WILEY-VCH.…”
Section: Chemotherapymentioning
confidence: 99%